Pengaruh Inteligensi Intrapersonal Terhadap Hasil Belajar Matematika Siswa - Nilam Permatasari Munir (Kelola: Journal of Islamic Education Management, 2017)
The study aims to analyze the descriprition of intrapersonal intelligence toward learning result of mathematics. The study is an ex-post facto which casuality. The populations of the study were 520 grade XI IPA students of SMAN in Parepare of academic years 2013/2014 with as many as 221 samples. Technique used in selecting the samples was proporsional random sampling. The instrument used for the study were (1) scale of intrapersonal intelligence, (2) test of mathematics learning outcomes. The results of the study indicate that (1) intrapersonal intelligence directly give positif influence toward cognitive learning result of Mathematics (5) intrapersonal intelligence directly give positif influence toward affective learning result of Mathematics.